Aerodynamic analysis of side-by-side placed twin vertical-axis wind turbines. (1st August 2020) - Jin, Guoqing; Zong, Zhi; Jiang, Yichen; Zou, Li
Abstract: The twin vertical-axis wind turbine (VAWT) system is a high-performance design in which two turbines are placed side by side with a variable gap distance. In this paper, the large eddy simulation and the sliding mesh technique are employed to numerically study the aerodynamic performance of the dual-rotor configuration. First, the reliability of this CFD model is validated, including computational stability analysis, time-step dependency study, and grid convergence verification. The turbine power coefficients under different tip speed ratios are calculated and results exhibit a satisfactory agreement with the available experimental data. Then, the wind energy utilization of side-by-side placed twin VAWTs under different gap ratios and various azimuth angle shifts are investigated, respectively. The results reveal that compared with two isolated turbines, the power coefficient of a twin-turbine system has a significant enhancement. Moreover, the paper analyzes the mechanism for obtaining gains. In regard to the study of azimuth angle shifts between two adjacent turbines, this paper demonstrates that the blade azimuth angles of twin VAWTs do not need to be synchronized. The azimuth angle shift has little effect on the aerodynamic performance of the twin-turbine system. Highlights: The power coefficient can be increased by 18% by applying the twin-turbine system. A smaller gap distance between two VAWTs can induce a larger power output. The phase angle of two turbines has little effect on the aerodynamic performance.